Pelatihan Tenaga Medis Dalam Pengolahan Limbah B3 Di Fasilitas Kesehatan Kesehatan Klinik Azzahra - Marthia Ikhlasiah (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Community service activities in the form of counselling are a form of community service through the provision of assistance for empowerment, training, counselling, guidance and to improve the quality of life. Observation is carried out using the interview method and looking directly at the field. Based on observations and identification of problems at Az-zahra Tangerang Primary Clinic in 2023. Therefore, one of the work programs, namely "Advisory Program on Factors Related to Nurse Behavior in Medical Waste Management Efforts in 2023" was determined. Therefore, after the community service activities are over, it is hoped that the work program that has been given can be used by the workforce and can continue continuously and maintain to equip themselves as provisions in the future